2013
DOI: 10.3171/2012.10.jns12747
|View full text |Cite
|
Sign up to set email alerts
|

Nervus intermedius dysfunction following Gamma Knife surgery for vestibular schwannoma

Abstract: The authors demonstrated that 22% of patients undergoing modern GKS for vestibular schwannoma experience various disturbances of nonmotor components of the facial nerve as a result of the radiosurgery. Through this study, we can provide useful information about the likelihood of certain postradiosurgical symptoms for vestibular schwannoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…1,8,15,22 The disturbances to functions of the nonmotor portions of the facial nerve after VS surgery or radiosurgery have been sporadically reported in the literature. 13,14,16,20,21,24 In this study, we present a prospective analysis of the clinical aspects of the dysfunctions of the nonmotor portion of the facial nerve after VS surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,8,15,22 The disturbances to functions of the nonmotor portions of the facial nerve after VS surgery or radiosurgery have been sporadically reported in the literature. 13,14,16,20,21,24 In this study, we present a prospective analysis of the clinical aspects of the dysfunctions of the nonmotor portion of the facial nerve after VS surgery.…”
Section: Discussionmentioning
confidence: 99%
“…of VS. 14,20,24 Some studies depended on self-assessment questionnaires mailed to the patients. 14,20 The taste sensation in cases of VS could be objectively tested using taste strips 4,9 or solutions. 16 It could also be tested using electrogustometry.…”
mentioning
confidence: 99%
“…One study found that 18% of vestibular schwannoma patients had nervus intermedius dysfunctions of lacrimation, salivation, nasal secretion, or taste prior to radiosurgery, increasing to 18 (36%) of 50 after radiosurgery. 4 This suggests that both the primary tumor itself and the treatment of the tumor can lead to disruption of nervus intermedius pathways. Once the normal neurologic pathways have been damaged, cross-innervation can occur, even before surgery, as evidenced by our first patient.…”
Section: Discussionmentioning
confidence: 99%
“…In this patient, the tumor has not grown significantly over several months with intact, meaningful hearing in place. This tumor based on the location is not removable without sacrificing hearing; therefore, repeat MRI every 6-12 months is warranted to observe for any changes that may warrant surgical removal, while ongoing hearing evaluations are conducted to allow the patient to enjoy intact function for as long as possible nervus intermedius, manifested as disturbances in taste, salivation, or lacrimation (22-45 %), has been documented despite normal facial nerve motor function [59].…”
Section: Complicationsmentioning
confidence: 99%
“…Non-obstructive hydrocephalus may be secondary to radiation-induced tumor necrosis and release of tumor proteins into CSF that impairs resorption by arachnoid granulations [54]. Hydrocephalus requiring a ventricular shunt occurs in up to 7 % of cases [40,52,53,59] and at higher rates with larger VS [42,43,60,61].…”
Section: Complicationsmentioning
confidence: 99%